Perancangan Automatic Tail Dock Berbasis Arduino Nano Pada Pesawat Menggunakan Metode PID - Irsyad Aziz; Andrijani Sumarahinsih; Delila Cahya Permatasari (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
The aviation industry is one of the service sectors. Due to its large number of users, safety is the primary concern in this industry. To ensure this safety, routine maintenance of operating aircraft is crucial, leading to the emergence of the aircraft maintenance industry. Due to the safety factors of the workpiece, installing ladders requires a significant workforce to supervise the workpiece, namely the aircraft itself, to prevent the ladder from hitting the aircraft body, which can result in COPQ (Cost Of Poor Quality). However, the use of many workers for ladder installation is considered inefficient because the maintenance process could be expedited if these workers could be utilized to install ladders on other parts of the aircraft. Therefore, if maintenance can be completed more quickly, the aircraft can return to flight sooner, meeting the airline's flight demands. Addressing this issue, this study aims to facilitate the ladder installation and removal process, thereby reducing the potential for collisions and ensuring the ladder is positioned at the required distance. This is achieved through ultrasonic sensors mounted on the work ladder, connected to a motor via Arduino Uno. The motor will stop when the input from the ultrasonic sensor reaches the predetermined distance. Additionally, if the aircraft tail moves while the ladder is installed, the system will automatically adjust the ladder's position to maintain the necessary distance, thus minimizing losses during aircraft maintenance.